A prospective follow-up study of younger and older subjects with pathological gambling. (October 2017) - Black, Donald W.; Coryell, William; McCormick, Brett; Shaw, Martha; Allen, Jeff
Abstract: Pathological gambling (PG) is a common and costly public health problem associated with impaired quality of life and high suicide rates. Despite its frequency in the general population, PG course is poorly understood in older adults who are especially vulnerable to its devastating consequences. We enrolled 175 subjects in a longitudinal study of gambling behavior: our case group of 53 older adults with PG (≥ 60 years), and two comparison groups including 72 younger adults with PG (< 40 years) and 50 older adults without PG (≥ 60 years). Subjects with PG met lifetime criteria for DSM-IV PG and had a South Oaks Gambling Screen (SOGS) and National Opinion Research Center DSM Screen for Gambling Problems (NODS) scores ≥ 5. Subjects were evaluated at intake and reassessed every 6 months and drop outs were replaced. Follow-up lasted a mean (SD) of 2.6 (1.4) years. At intake older PGs were more likely to be female, Caucasian, divorced, and to have a lower level of education. Older and younger PGs were similar in gambling severity, but older PGs were more likely to have sought PG treatment. Older PGs had lower rates of lifetime drug use disorders, attention deficit/hyperactivity disorder, and obsessive-compulsive disorder. They preferred slots, were more likely to receive PG treatment, and were less likely to discontinue participation in the study. Week by week gambling activity levels showed a significant general downward movement for older and younger PGs, although there were no differences between the groups. Elders without PG had no change in their level of gambling activity. We conclude that younger and older PGs moved toward a reduced level of gambling activity during follow-up. Our data challenge the notion that PG is chronic and progressive. Highlights: Seventy-two younger (< 40 years) and 50 older (≥ 60 years) subjects with pathological gambling (PG), and 53 older adults without PG were systematically interviewed every 6 months. Older PGs were more likely to be female, Caucasian, divorced, and to have a lower level of education. Older PGs had lower rates of lifetime drug use disorders, attention deficit/hyperactivity disorder, and obsessive-compulsive disorder. They preferred slots, had worse physical health ratings. Week by week gambling activity levels showed a significant general downward movement for older and younger PGs, although there were no differences between the groups. Our data challenge the notion that PG is chronic and progressive.